DITERMINAN KINERJA PEMERINTAH DESA - Herry Purnomo; Qaiyim Asy’Ari; Nurharibnu Wibisono; Arini Wildaniyati; Nensi Putri Chintianila (Universitas Merdeka Madiun, 2026)
Abstract— This paper seeks to empirically assess the key variables affecting performance within village government structures in Karas District, Magetan Regency. The independent variables of the study are Regulation, Organizational Commitment, and Human Resources (HR). and Leadership. The current analysis identifies Village Government Performance as the core dependent variable. The research population is Village Apparatus and the sampling technique uses purposive sampling, that is the Village Head, Secretary, Treasurer, Section Head, Head of Affairs, and village operators who are directly involved in village financial management. The research data were obtained from questionnaires from 60 respondents from 11 villages in Karas District, Magetan Regency. The research data analysis used Multiple Linear Regression with Smart PLS 4 tool. The empirical findings demonstrate that while organizational commitment and leadership exert a significant influence on village government performance. Regulation and human resources do not show a statistically significant effect on village government performance.. Village officials and village office staff need to understand and comply with applicable regulations and improve HR capacity so that public budget management can run efficiently, effectively, and accountably. As an agent, the Village Government needs to realize a just, prosperous village society and optimize the delivery of administrative services to the public.